New Geographical Insights of the Latest Expansion of Fusarium oxysporum f.sp. cubense Tropical Race 4 Into the Greater Mekong Subregion - Zheng, Si-Jun; García-Bastidas, Fernando A.; Li, Xundong; Zeng, Li; Bai, Tingting; Xu, Shengtao; Yin, Kesuo; Li, Hongxiang; Fu, Gang; Yu, Yanchun; Yang, Liu; Nguyen, Huy Chung; et al. (Frontiers in Plant Science, 2018)
Banana is the most popular and most exported fruit and also a major food crop for millions of people around the world. Despite its importance, research into this crop is limited and hence, it suffers from major disease threats. One of those is Panama disease or Fusarium wilt. In the previous century Fusarium wilt wiped out the “Gros Michel” based banana industry in Central America. The epidemic was eventually quenched by planting “Cavendish” bananas. However, 50 years ago the disease recurred, but now on “Cavendish” bananas. Since then the disease has spread across South-East Asia, to the Middle-East and the Indian subcontinent and leaped into Africa. Here, we report the presence of Fusarium oxysporum f.sp. cubense Tropical Race 4 (Foc TR4) in “Cavendish” plantations in Laos, Myanmar and Vietnam. A combination of classical morphology, DNA sequencing and phenotyping assays revealed a very close relationship between the Foc TR4 strains in the entire Greater Mekong Subregion (GMS), which is increasingly prone to intensive banana production. Analyses of single-nucleotide polymorphisms enabled us to initiate a phylogeography of Foc TR4 across three geographical areas - GMS, Indian subcontinent and the Middle East revealing three distinct FocTR4 sub-lineages. Collectively, our data place these new incursions in a broader agroecological context and underscore the need for awareness campaigns and the implementation of validated quarantine measures to prevent further international dissemination of Foc TR4.